The Relationship between the Use of Hormonal Contraceptive Devices on Body Weight of Family Planning Acceptors - Arna Arna; Narmawan Narmawan; Muhammad Syaiful Saehu; Muhammad Jasmin (KLASICS, 2022)
Contraception is a way to prevent and space pregnancies as well as to plan the number of children to improve family welfare so that they can provide maximum attention and education to children. The level of contraceptive use or the Contraceptive Prevalance Rate (CPR) in Indonesia was 57% in 2015 to 61.4% in 2018. This study aims to determine the relationship between the use of hormonal contraceptives and the body weight of family planning acceptors. This type of research is a descriptive analytic study with a cross sectional research design. This research was conducted in the working area of the Landawe Health Center in August 2021. The analysis used the Fisher exact test. The results showed that most of the respondents' weight increased by 60%. The results of the analysis show that value is 0.032 < = 0.05, which means that there is a relationship between the use of hormonal contraception and body weight in family planning acceptors.